Analysis of Volatile Oil of Fritillaria cirrhosa D. Don by GC-MS - Wang, Xiaojing; Li, Yumei (Asian Journal of Chemistry, 2013)
The volatile oil was extracted from Fritillaria cirrhosa D. Don by water steam distillation and the chemical constituents of volatile oil separated were identified by gas chromatography-mass spectrometry analysis. The relative content of the constituents from the volatile oil were determined by area normalization method. Thirty-nine peaks were separated, among which 14 compounds were identified, amounting to 81.92 % of the total amount of volatile oil. The main compounds identified to be 1-octadecene (16.38 %), 1-dodecene (15.09), oxirane, hexadecyl-(11.38 %), 1-hexadecanol (10.65 %), 1-eicosanol (7.95 %), 9-octadecynoic acid, methyl ester (6.94 %), n-hexadecanoic acid (5.41 %). The work provides information for making full use of the Fritillaria cirrhosa D. Don resources and pharmacological activities research of traditional Chinese medicine.